Effects of a Research Potential Development Program on the Use of Research Utilization and Satisfaction of Nurse in Regional Hospital in Southern - สิงห์ช่างชัย, เพชรน้อย; อิงคถาวรวงศ์, ฐิติพร; หนุนพระเดช, ปาริชาติ; เจริญสิน, สุทิศา (Al-HIKMAH Journal, 2018)
This quasi-experimental research with a pre-post design aimed to investigate the effects of a researchers’ utilization program on the use of research results and satisfaction of nurses at Hat Yai Central Hospital. The subjects were 100 nurses from units of the Nursing Section of Hat Yai Central Hospital. Four types of instrument were used: 1) a researchers’ potential development program, 2) a manual for research quality assessment for selecting nursing research for use consisting of five learning units, 3) a questionnaire asking about knowledge of the use of research results for service quality development before and after using the program, 4) a questionnaire asking satisfaction towards nurses’ potential development program for the use of research results. The quality of the instruments were tested for content validity by three experts. The reliability was tested using Cronbach’s alpha and the coefficient of reliability was 0.99 and the KR-21 coefficient of reliability was 0.8. General data and satisfaction were analyzed with frequency, percentage, mean, standard deviation, and paired t-test. When the average scores for knowledge of the use of research results were compared, it was found that the scores before and after the use of the program were significantly different (p<.05). After using the program, the subjects were satisfied with the program at a very high level (M = 2.66, SD.=1.06). When considered by item, it was found that the subjects were most satisfied with five aspects, very satisfied with three aspects, and moderately satisfied with two aspects. The nurses were satisfied at a high level in three aspects (the program activities being in line with organizational policy, learning activities related to the application of research results development program, and support in follow ups of the potential to apply research results). They were satisfied at a moderate level in two aspects (length of time, and manual and related documents).Hospital administrators should be identify the development methods for professional nurses so that they use results of nursing research and health research to develop health service quality in government hospital to save the limited time that professional nurses have, to save budget for searching new knowledge, and to increase cost-effectiveness of research.